Specifications for particular types of winding wires. Polyester glass fibre wound minimum class 155 resin or varnish impregnated or not impregnated, bare or enamelled, rectangular copper wire, temperature index 155 Part 60, (31st August 2012) - British Standards Institution,
No abstract available